Pattern of deep neck space infections at a tertiary hospital, Kathmandu, Nepal - Maharjan, Shova; Joshi, RR; Rijal, AS; Dhungana, A; Shrestha, KK (Nepal Medical College Journal, 2020)
Deep neck space infection is characterized by infections of the deep neck space either in the form of abscess or cellulitis. Common infective conditions like aero-digestive tract infections like tonsillitis, pharyngitis and dental infections can lead to infection of the deep neck spaces. This can prove fatal in the form of acute respiratory obstruction, descending mediastinitis and septic shock. This was a descriptive cross-sectional study conducted in Department of Otorhinolaryngology in Nepal Medical College from July 2017 to June 2019. All the patients diagnosed as deep neck abscess were enrolled in the study and pus was collected and sent for gram stain and culture and sensitivity. Out of 87 patients, 50 were females and 37 males. The mean age was 24.2 years. Peritonsillar abscess was the commonest space involved followed by submandibular abscess and Ludwig’s angina (36.8%,24.1% and 11.5%). Upper respiratory tract infections (32.2%) and dental caries (27.6%) were the commonest source of infection. Empyema thoracis was seen as a complication in a patient of Ludwig’s angina. Growth in the sample accounted for 33.3%. The commonest organism found was Coagulase negative Staphylococcus (10.3%), followed by Mycobacterium tuberculosis (6.9%), Staphylococcus aureus (4.6%), Enterococcus species (3.4%) and methicillin-resistant S. aureus (3.4%) respectively. The growth between the culture with or without previous antibiotic exposure were statistically significant (p-value-0.04) which suggest that inadvertent use of antibiotics lead to difficulty in identifying causative organism. Deep neck abscess is a dreadful condition, therefore proper knowledge, early detection and timely intervention of the disease can prevent complications.